2023
DOI: 10.2478/jtim-2022-0074
|View full text |Cite
|
Sign up to set email alerts
|

Short-term duration of diabetic retinopathy as a predictor for development of diabetic kidney disease

Jiayu Duan,
Dongwei Liu,
Zihao Zhao
et al.

Abstract: Background Diabetic retinopathy (DR) is a risk factor for diabetic kidney disease (DKD). Whether the duration, especially the short-term duration, of DR is associated with the development and progression of DKD remains unclear. Materials and Methods A retrospective study and two-sample Mendelian randomization (MR) analysis were conducted. Kidney disease was defined by the urinary albumin-to-creatinine ratio (ACR) and the esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Our analysis also revealed that baseline eGFR and the stage of AKI at the time of enrollment emerged as significant variables influencing the progression of AKI to stage 3 or mortality. These findings align with previous studies that have consistently demonstrated pre-existing chronic kidney disease, as indicated by reduced eGFR, to be a robust risk factor for AKI, dialysis, and mortality [ 29 31 ]. Furthermore, the AKI stage at enrollment appeared to reflect the severity of renal insult and exhibited a definite association with unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis also revealed that baseline eGFR and the stage of AKI at the time of enrollment emerged as significant variables influencing the progression of AKI to stage 3 or mortality. These findings align with previous studies that have consistently demonstrated pre-existing chronic kidney disease, as indicated by reduced eGFR, to be a robust risk factor for AKI, dialysis, and mortality [ 29 31 ]. Furthermore, the AKI stage at enrollment appeared to reflect the severity of renal insult and exhibited a definite association with unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a retrospective study of deep fungal infections in elderly individuals found that diabetic patients were prone to developing invasive candidiasis, while invasive aspergillosis was less prevalent ( 4 ). Despite the established connection between diabetes and bacterial infections, the association between T1DM and mycoses remains a less explored area, presenting an intriguing path for future study ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a retrospective study of deep fungal infections in elderly individuals found that diabetic patients were prone to developing invasive candidiasis, while invasive aspergillosis was less prevalent (4). Despite the established connection between diabetes and bacterial infections, the association between T1DM and mycoses remains a less explored area, presenting an intriguing path for future study (5).…”
Section: Introductionmentioning
confidence: 99%